Making a building budget in Building Information modeling system Juraj Talian - Talian, J. (Видавництво Львівської політехніки, 2011)
Parametric modeling has been proposed as an effective means to creation construction projects. One of the new approaches using the parametric modeling is Building Information Modeling. Parametric dates from the virtual model (virtual building) are not only construction-material base but more specific like construction costs, construction time and etc. This paper focuses attention on the creation of the budget in concept and design phase using the parametric modeling.
Розробка кошторисів будівництва у системі інформаційного моделювання будинків (BIM)
Keywords: Building Information Modeling; cost; budget; CAD application